Left-Handedness Among Orthopaedic Surgeons and Trainees. Issue 2 (April 2020) - Sabharwal, Samir; MacKenzie, James S.; Sterling, Robert S.; Ficke, James R.; LaPorte, Dawn M.
Abstract : Background: The impact of left-handedness on orthopaedic surgeons and trainees has not been well described. We investigated the prevalence and perceived impact of left-handedness among orthopaedic surgeons and trainees. Methods: We distributed a survey regarding handedness to active members of the American Orthopaedic Association and the Council of Orthopaedic Residency Directors affiliates, including department chairs, program directors, and residency and fellowship program coordinators. Program coordinators were asked to distribute the survey to their current residents and fellows. Results: Of 510 survey respondents, 78 (15%) were identified as left hand dominant (LHD). Regarding scalpel/cautery use, 64% of LHD respondents reported using their left hand primarily and 10% reported using their right hand primarily; 26% of LHD respondents described themselves as ambidextrous in scalpel/cautery use, compared with 4.7% of right hand dominant (RHD) respondents (p < 0.001). Regarding suturing, 53% of LHD respondents reported using their left hand primarily and 38% reported using their right hand primarily; 9.0% of LHD respondents described themselves as ambidextrous when suturing, compared with 1.9% of RHD respondents (p = 0.012). Only 5.1% of LHD respondents reported having received laterality-specific psychomotor training, whereas 17% perceived a need for such training during residency; RHD respondents reported similar rates. Ambidexterity in scalpel/cautery use or suturing among LHD respondents was not associated with the perception that their left-handedness was advantageous. LHD attending surgeons were more likely than LHD trainees to perceive their handedness as advantageous (p = 0.007). Conclusions: Fifteen percent of orthopaedic surgeons and trainees who responded to our survey were LHD. LHD respondents reported significantly higher rates of ambidexterity in both scalpel/cautery use and suturing compared with RHD respondents. Ambidexterity was not associated with a self-perception that left-handedness was advantageous. LHD-attending surgeons were significantly more likely than LHD residents/fellows to perceive their left-handedness as advantageous. There may be benefits to pairing LHD residents with LHD faculty surgeons early in their training to provide mentorship and insight regarding performing surgical procedures left handed. Level of Evidence: Level IV.